Privatisation and the Creation of a Market-Based Legal System : The Case of Egypt - El-Dean, Bahaa Ali, (Social, Economic and Political Studies of the Middle East and Asia ;, 2002)
The creation of a legal infrastructure that suits the needs and potential of emerging economies is a conditio sine qua non for the long term success of a privatisation process. The purpose of this Volume is to examine and evaluate efforts of legal reform, through the analysis of legal changes in several areas of law, including securities regulation, competition law, the law on secured transactions and bankruptcy law. The study aims at assessing the overall difficulties affecting the creation of a market based legal system for emerging economies, and concludes by providing several recommendations and suggestions which are relevant to most countries and institutions engaged in the privatisation process.